2016
DOI: 10.4067/s0717-95022016000100042
|View full text |Cite
|
Sign up to set email alerts
|

3-D Structural Changes in Subchondral Bone and the Effect of Bisphosphonate Intervention in Early Osteoarthritis

Abstract: SUMMARY:This study aims to observe the 3-D structural changes in subchondral bone and the effects of bisphosphonate intervention in the early unsteady stage of the knee joint. Sixty healthy male New Zealand white rabbits were divided into the model group (n= 24), the bisphosphonate (Bis) group (n= 24), and the control group (n= 12). The rabbits' right knees were used to evaluate the structural changes. The Bis group received subcutaneous injections of bisphosphonate, while the model and control groups received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Regarding the mechanisms by which bisphosphonates may have beneficial effects on OA progression, it has been suggested that these drugs might lead to local improvement in periarticular bone strength through reducing bone turnover, which would improve load absorbance; and therefore, reduce the biomechanical stress on the overlying cartilage and subsequently reduce cartilage breakdown 2,5 . This hypothesis has been primarily evaluated in a few clinical studies that showed a diminished periarticular trabecular bone loss in bisphosphonates users 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the mechanisms by which bisphosphonates may have beneficial effects on OA progression, it has been suggested that these drugs might lead to local improvement in periarticular bone strength through reducing bone turnover, which would improve load absorbance; and therefore, reduce the biomechanical stress on the overlying cartilage and subsequently reduce cartilage breakdown 2,5 . This hypothesis has been primarily evaluated in a few clinical studies that showed a diminished periarticular trabecular bone loss in bisphosphonates users 13 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that bisphosphonates may target the periarticular bone, which plays a pivotal role in the pathogenesis of OA and has been introduced as a biomarker of OA progression 4 . By inhibiting osteoclastic bone resorption and cellular secretion of transforming growth factor-b and matrix metalloproteinases, which are responsible for the cleavage of type II collagen; bisphosphonates may reduce periarticular bone turnover and lead to the local preservation of bone strength and microarchitecture, and eventually minimize OA progression 2,5 .…”
Section: Introductionmentioning
confidence: 99%